Profile of Doctoral Student’s Motivation in Science Education Program: A Mini Research - Arina Zaida Ilma; Ananda Aprilia; Dwi Purbowati; Susdarwati Susdarwati; Putri Anjarsari; Widodo Setiyo Wibowo; Norma Bastian; Rita Bekti Utami (International Journal of Science and Applied Science: Conference Series, 2024)
The evolving landscape of higher education and its potential implications for the careers of doctoral graduates is growing. This research aims to analyze the motivation profiles of doctoral students in a Science Education program. Survey data was collected from students enrolled in the Science Education Doctoral Program at Universitas Negeri Yogyakarta in the 2024/2025 academic year. Ten question surveys with qualitative open-ended questions were developed in this research. Findings highlight intrinsic, integrated, and identified motivational factors and their potential implications for educational practices in doctoral programs in science education. The recommendations provided institutions to design more effective support strategies to ensure the academic success and contribution of doctoral students to the advancement of science education in Indonesia.